KAJIAN OPTIMASI KOMBINASI LDPE, CPO, BAN DALAM SEBAGAI PENGIKAT TERHADAP CAMPURAN AC-WC - Refiyanni, Meidia; Opirina, Lissa; Ikhsan, Muhammad; Azwanda, Azwanda; Satria, Andrisman; Tripoli, Bambang (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2024)
Abstract Infrastructure development continues to increase, especially on highway pavement, requiring a lot of materials such as coarse aggregate, fine aggregate, filler and asphalt (Pen 60/70) as a binder. However, the depletion of petroleum reserves which has an impact on the availability of asphalt has encouraged innovation to reduce its use. One potential innovation is the use of a combination of plastic waste (LDPE), Crude Palm Oil (CPO), and used inner tubes as an alternative binding material. This research examines the optimization of the use of this combination in the Asphalt Concrete-Wearing Course (AC-WC) mixture. Indonesia, as a tropical country with a significant area of oil palm plantations, produces abundant CPO. In addition, high use of plastic produces plastic waste that is difficult to decompose, and Indonesia is one of the largest contributors of plastic waste in the world. By utilizing this waste in road pavement, this research seeks to reduce environmental impacts while providing alternative solutions for pavement materials. Tests were carried out with three variations, namely V1 = 3% LDPE : 2% CPO : 10% inner tube : 85% pen 60/70;  V2 = 4%LDPE : 2%CPO : 10% inner tube : 84% pen 60/70; V3 = 5%LDPE : 2%CPO : 10% inner tube : 83% pen 60/70 to determine the characteristics of stability, flow, VMA, Void in Mix (VIM), VFB, and Marshall Quotient (MQ). The test results show that the Optimum Asphalt Content (KAO) value is 5.5%. All variations meet the minimum stability specifications set by Bina Marga(2018). Keywords : LDPE, CPO, Karet Ban Dalam, Pen 60/70, AC-WC